An expanding role for purine uptake permease-like transporters in plant secondary metabolism - Jelesko, John G. (Frontiers in Plant Science, 2012)
For the past decade, our understanding of the plant purine uptake permease (PUP) transporter family of was primarily oriented on purine nucleobase substrates and their tissue-specific expression patterns in Arabidopsis. However, a tobacco PUP-like homolog demonstrating nicotine uptake permease (NUP) activity was recently shown to affect both nicotine metabolism and root cell growth. These new findings expand the physiological role for PUP-like transporters to include plant secondary metabolism. Molecular evolution analyses of PUP-like transporters indicate they are distinct group within an ancient super family of drug and metabolite transporters (DMTs). The PUP-like family originated during terrestrial plant evolution sometime between the bryophytes and the lycophytes. A phylogenetic analysis indicates that the PUP-like transporters were likely were derived from a pre-existing nucleotide sugar transporter family within the DMT super family. Within the lycophyte Selaginella, there are three paralogous groups of PUP-like transporters. One of the three PUP-like paralogous groups showed an extensive pattern of gene duplication and diversification within the angiosperm lineage, whereas the other two more ancestral PUP-like paralogous groups did not. Biochemical characterization of four closely-related PUP-like paralogs together with model-based phylogenetic analyses indicate both subfunctionalization and neofunctionalization during the molecular evolution of angiosperm PUP-like transporters. These findings suggest that members of the PUP-like family of DMT transporters are likely involved in diverse primary and secondary plant metabolic pathways.